Effect of Brain Gym Exercises on Risk of Fall, Balance and Quality of Life in Obese Subjects. - Elerian, Aya Abdelhady; Elkeblawy, Maher Ahmed; Lasheen, Yasser Ramzy; Abdelhay, Mohamed Ibrahim (Physiotherapy Research International, 2026)
Background and Purpose: Obesity is a widespread global health problem linked to an elevated risk of falls, detrimental effects on both static and dynamic balance, and diminished quality of life (QOL). Despite these adverse effects of obesity, research on the effectiveness of Brain Gym exercises has been conducted in various populations, but their impact has never been studied among individuals with obesity. Methods: A pre‐post randomized controlled trial aimed to examine the influence of Brain Gym exercises on fall risk, balance, as well as quality of life among obese individuals. Thirty‐two subjects (15 males and 17 females) aged 18–50 years, with a Body Mass Index (BMI) of ≥ 30 kg/m2 were randomly assigned to two equal groups, Group A (experimental): engaged in Brain Gym exercises for 30 min daily, three times weekly, for eight successive weeks, in addition to conventional balance training for 45 min throughout three sessions per week for eight weeks. Group B (control): received conventional balancing training. Outcome measures included: risk of falling assessed using the Modified Arabic version of the Activities‐Specific Balance Confidence Scale (ABC); static balance evaluated via the Berg Balance Scale (BBS); dynamic balance assessed with the Balance Check 636 Stability Tester (Dr. Wolff, Arnsberg, Germany); as well as health‐related quality of life determined through the Arabic version of the World Health Organization Quality of Life‐BREF questionnaire (WHOQOL‐BREF). Results: The results indicated substantial enhancements in all assessed outcomes, including risk of falling, static balance, dynamic balance, and quality of life domains, in both groups following treatment (p < 0.001). The experimental group demonstrated statistically and clinically significant improvements in all parameters relative to the control group (p < 0.001). Discussion: Brain Gym exercises combined with conventional training could have a further impact on the risk of fall, balance as well as quality of life among obese subjects than conventional balance training alone. Trial Registration: NCT06587932